Reporting of Aedes (Stegomyia) albopictus (Skuse, 1895) in the Territory of Crimea - I. S. Kovalenko; S. N. Yakunin; D. E. Abibulaev; V. V. Vladychak; N. V. Boroday; V. P. Smelyansky; V. K. Fomina; L. S. Zinich; S. N. Tikhonov (Проблемы особо опасных инфекций, 2020)
Abstract. Detection of epidemiologically significant mosquitoes Ae. аlbopictus in the south of Russia (the Greater Sochi region, the Black Sea coast of Caucasus) suggested the possibility of their introduction into Crimea.Objective was to determine the possibility of existence of epidemically significant vector – mosquito Ae. albopictus inCrimea.Materials and methods. Within the frames of entomological monitoring, mosquitoes were collected during May-October, 2018 and May-September, 2019 in different regions of Crimea: Bakhchisaray, Dzhankoy, Razdolnensky, Saksky, Black Sea regions, urban areas ofSimferopol,Sevastopol and Feodosiya. Fully-grown mosquitoes were caught by automatic trap Mosquito Magnet Executive (USA) with octenol-based bait. Actively attacking females were collected with an aspirator by Gutsevich method. The survey was conducted in the evening and night hours. A total of 26 visits were made, 77 hours were spent, and 8463 mosquitoes (adult and larvae) were captured.Results and discussion. During entomological monitoring of the territory of Crimean Peninsula for the first time bloodsucking mosquitoes Aedes (Stegomyia) albopictus (Skuse, 1895) were found. Given the favorable climatic conditions in Crimea, the trend towards global warming, the adaptation of mosquitoes to the periods of cold, biology of Aedes albopictus, the distribution of this species in the European part of southern Russia, the formation and dissemination of sustainably replicating vector population on the Crimea Peninsula is possible. To confirm the circulation of independent Ae. albopictus population inCrimea, not a random import of adult specimens who die in winter, further entomological surveys are required on a regular basis.